The Pivotal Impact of Technology Integration in Primary Education - Mahi Sultan Salama; Kristiyuana Kristiyuana; Esty Setyo Utaminingsih (Universitas Negeri Semarang, 2025)
The research investigates technology integration in elementary education, focusing on teachers' experiences, challenges, and strategies in Semarang City and Blora Regency, Indonesia. As technology rapidly evolves, its application in education becomes increasingly vital, yet the effective integration of digital tools remains a challenge in many primary schools. Teachers' perspectives and practices are critical in shaping how technology impacts learning outcomes. The primary objective of this study is to explore the various strategies teachers employ in integrating technology into the classroom, identify the challenges they encounter, and assess the overall impact of technology on students' learning experiences. A qualitative research method was used, employing in-depth interviews and classroom observations with elementary school teachers from selected schools in Semarang and Blora. The findings reveal that while teachers recognize the potential of technology in enhancing learning, they face several challenges, such as limited resources, insufficient training, and resistance from students or parents. However, many teachers have developed innovative strategies to overcome these obstacles, incorporating various digital tools to foster interactive and engaging learning environments. In conclusion, the research highlights the need for more comprehensive support, professional development, and resource allocation to integrate technology into elementary education effectively. This study provides valuable insights for policymakers and educators to enhance technology adoption and improve primary school educational practices.